2015
DOI: 10.1007/s12402-015-0170-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and nitrosative stress in ADHD: possible causes and the potential of antioxidant-targeted therapies

Abstract: Attention deficit hyperactivity disorder (ADHD) has a complex etiology although theories associated with disturbances in dopaminergic and noradrenergic activity are most commonly cited.The importance of these catecholamines in ADHD is supported by its effective treatment utilising stimulant and non-stimulant medications that modify their activity. Recently there has been interest in oxidative and nitrosative stress (O&NS) in ADHD and its potential to contribute to this condition. In this article, research inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 118 publications
2
38
0
2
Order By: Relevance
“…Although there are inconsistent results regarding the relationship of oxidative stress and ADHD, in a meta-analysis it was confirmed that ADHD is associated with increased oxidative stress in ADHD patients [16]. Taken together, the data suggest that both oxidative and nitrosative stress in ADHD have the potential to contribute to this condition [15].…”
Section: Oxidative Stress and The Relationship With Adhdmentioning
confidence: 89%
See 2 more Smart Citations
“…Although there are inconsistent results regarding the relationship of oxidative stress and ADHD, in a meta-analysis it was confirmed that ADHD is associated with increased oxidative stress in ADHD patients [16]. Taken together, the data suggest that both oxidative and nitrosative stress in ADHD have the potential to contribute to this condition [15].…”
Section: Oxidative Stress and The Relationship With Adhdmentioning
confidence: 89%
“…Moreover, increasing evidence indicates a critical role for neuroinflammation [13,14]. Also, the involvement of oxidative stress is highlighted as a pathophysiological cause of ADHD [15,16].…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiências de minerais, como zinco, ferro, magnésio, e de vitaminas, como a vitamina D, têm sido reportadas em crianças com TDAH 16,17,20,22,23,24 , bem como têm sido observados níveis elevados de estresse oxidativo 14,25,26,27,28,29 . Caso a criança possua alguma deficiência/insuficiência nutricional suspeitada/documentada, esta deve ser tratada/ corrigida.…”
Section: A Criança Possui Alguma Deficiência/insuficiência Nutricionaunclassified
“…In addition, an overall dysfunction in the dopaminergic and noradrenergic system is involved in ADHD [ 9 , 10 , 11 ]. These catecholamines are active in brain areas involved in the regulation of attention and behavior [ 12 ]. Indeed, destruction of dopamine pathways in the prefrontal cortex resulted in hyperactivity [ 13 ], while concentrations of catecholamines are higher in the urine of ADHD patients compared to controls [ 14 , 15 ].…”
Section: Introduction: Attention-deficit Hyperactivity Disordermentioning
confidence: 99%